Adopting Feminist Pedagogy in Computer Science Education to Empower Underrepresented Populations: A Critical Review - Ren, Xinyue (TechTrends, 2022)
The participation and engagement of traditionally underrepresented students remained low in computer science subjects and career paths, especially women and women of color. In terms of the urgent need to achieve intellectual diversity within the computer science field, many institutions strived to broaden the participation of women and women of color in computer science programs. However, access does not mean success. Effective pedagogical interventions are essential to change the classroom culture to support the retention and completion of women students in computer science. Research showed the promise of feminist pedagogy in eliminating gendered stereotypes, biases, and oppressions perpetuated within computer science education. The purpose of this article is to discuss course design considerations while adopting feminist pedagogy to promote gender parity in computer science, as indicated in feminist consciousness, collaborative learning, and reflexive learning. Further research and interventions are needed to address inequality issues in computer science in other contexts.